2010
DOI: 10.1111/j.1365-2672.2010.04793.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of quorum-sensing system to hexadecane degradation and biofilm formation in Acinetobacter sp. strain DR1

Abstract: Aims:  To investigate roles of quorum‐sensing (QS) system in Acinetobacter sp. strain DR1 and rifampicin‐resistant variant (hereinafter DR1R). Methods and Results:  The DR1 strain generated three putative acyl homoserine lactones (AHLs), while the DR1R produced only one signal and QS signal production was abrogated in the aqsI (LuxI homolog) mutant. The hexadecane‐degradation and biofilm‐formation capabilities of DR1, DR1R, and aqsI mutants were compared, along with their proteomic data. Proteomics analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 48 publications
(88 reference statements)
2
46
0
Order By: Relevance
“…Interestingly, DR1 possesses a quorum sensing (QS) system, which has been shown to play a significant role in biofilm formation and hexadecane biodegradation. The results of proteomic studies have demonstrated that the QS system regulates a broad variety of proteins (6). Collectively, our findings demonstrate that DR1 has profound potential for environmental applications and is an environmental isolate distinct from pathogenic strains, thus indicating that the whole-genome sequencing of DR1 is a worthwhile pursuit.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Interestingly, DR1 possesses a quorum sensing (QS) system, which has been shown to play a significant role in biofilm formation and hexadecane biodegradation. The results of proteomic studies have demonstrated that the QS system regulates a broad variety of proteins (6). Collectively, our findings demonstrate that DR1 has profound potential for environmental applications and is an environmental isolate distinct from pathogenic strains, thus indicating that the whole-genome sequencing of DR1 is a worthwhile pursuit.…”
mentioning
confidence: 92%
“…There are 6 rRNA operons with a 16S, tRNA-Ile, tRNAAla, 23S, 5S organization. The genes studied previously were clearly identified via genome sequencing (4,5,6). The availability of the complete genome sequence of Acinetobacter sp.…”
mentioning
confidence: 99%
“…The genetics and physiology of strain DR1 (with respect to activities such as biodegradation of diesel fuel, biofilm formation, natural transformation, quorum sensing, and oxidative stress) have only begun to be investigated (16,19,20,21,30). The availability of the complete genome of strain DR1 (16) provides the opportunity for a comparative study.…”
mentioning
confidence: 99%
“…Although n-hexadecane degradation by Acinetobacter strains has been widely reported (Koma et al, 2001;Kang and Park, 2010), reports of Acinetobacter strains possessing heavy metal tolerance together with PAH degradation abilities are scarce. Acinetobacter strains tolerant to chromium, nickel and cadmium that are useful for heavy metal bioremediation have been described (Bhattacharya and Gupta, 2013).…”
Section: Discussionmentioning
confidence: 99%